(untitled) (CAHIERS MAGELLANES-NS, 2024)
Root canal irrigation solutions are basic to endodontic therapy especially for killing bacteria and softening tissue. Nevertheless, their toxicity levels are a great problem because in the event of an unfavorable reaction with periapical tissue and the general body, outcomes may be severe. This systematic review assesses the toxicity of the traditional RCIs including NaOCl, CHX, EDTA and emerging irrigants; plant-derived irrigants and nanoparticles. An extensive literature review for the articles published after 2019, which evaluated the cytotoxicity, genotoxicity, and biocompatibility of the mentioned solutions was performed across the relevant databases. The findings also reveal that although NaOCl maintains rather high bactericidal activity, it likewise exerts rather toxic impact on periapical tissues. CHX is less cytotoxic but has relatively low ability in tissue dissolution. Although smear layer removal is achieved more efficiently using EDTA, such material also depicts a diverse level of cytotoxicity based on its concentration in addition to the time for which it is applied. Exciting newly developing options, such as herbal irrigants and nanoparticles, show similar efficacy with less side effects. Nonetheless, large studies are required to develop consistent protocols regarding the effectiveness and safety of root canal irrigation.